2019
DOI: 10.1111/1744-9987.13455
|View full text |Cite
|
Sign up to set email alerts
|

Higher Cholesterol Level Predicts Cardiovascular Event and Inversely Associates With Mortality in Hemodialysis Patients: 10‐Year Outcomes of the Q‐Cohort Study

Abstract: The prevalence of atherosclerotic diseases is higher in hemodialysis patients. The aim of the current study was to investigate associations between cholesterol level and the incidences of cardiovascular disease (CVD) and mortality in hemodialysis patients. A total of 3517 participants undergoing maintenance hemodialysis were followed up for 10 years. Total cholesterol (TC) level was divided into quartile in baseline data. The multivariate analyses were calculated by a Cox proportional hazards model. The incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Furthermore, an observational study that followed hemodialysis patients for 10 years reported that the risk of cardiovascular events increased as cholesterol levels increased. This finding indicates that an intensified cholesterol-lowering treatment may be necessary to reduce the risk of CVD [28]. Of interest, in this study, 3 months of high-dose EPA/DHA reduced RLP-C by approximately 46%, whereas a randomized controlled trial of cilostazol for 6 months in patients with intermittent claudication (n = 56) reduced RLP-C by approximately 20% [29].…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, an observational study that followed hemodialysis patients for 10 years reported that the risk of cardiovascular events increased as cholesterol levels increased. This finding indicates that an intensified cholesterol-lowering treatment may be necessary to reduce the risk of CVD [28]. Of interest, in this study, 3 months of high-dose EPA/DHA reduced RLP-C by approximately 46%, whereas a randomized controlled trial of cilostazol for 6 months in patients with intermittent claudication (n = 56) reduced RLP-C by approximately 20% [29].…”
Section: Discussionmentioning
confidence: 71%
“…Studies have shown that reducing LDL-C levels did not improve overall survival in either HD patients or the general population 3 16 17. Moreover, lower TC was discovered to be a risk factor for death and was linked to a poor prognosis in maintenance HD patients 18 19. A previous study showed that hypertriglyceridaemia is paradoxically related to better survival 5.…”
Section: Discussionmentioning
confidence: 99%
“…More than two decades ago, a study of more than 12,000 hemodialysis patients reported that all-cause mortality risk was significantly lower at higher total cholesterol levels [ 6 ]. Since then, many prospective studies in hemodialysis patients have replicated this inverse association [ 15 , 16 ]. A similar inverse association was observed among PD patients.…”
Section: Discussionmentioning
confidence: 99%